Environmental remediation of dye effluents using Gracilaria edulis (Marine red alga) mediated green synthesized Ag₂O nanoparticles: Impacts on soil and water quality - G. Visu; N. Muruganantham; P. Anitha; R. Govindharaju; V. Anusuya (Environmental Nanotechnology, Monitoring & Management, 2026)

Chemometric and computational structure–activity relationship analysis of Ziziphus jujuba and Nephrolepis cordifolia phenolics for antioxidant and antidiabetic potential - Anitha A․; Ponmurugan P․; Arunkumar D․; Vasantha Sakthi S․; Yamuna A․; Jeyapreethi S․ (South African Journal of Botany, 2026)

Association Mapping of Height- and Yield- Related Traits using SSR Markers in Four Oil Palm (E. guineensis Jacq.) Populations - B. Kalyana Babu; G. Ravichandran; K. Suresh; Sandip Shil; Sarika Sahu; Narayana Ruthwek; Mokhamatla Mahesh; P. Anitha; M. Peeyusha Sai (Journal of Plant Growth Regulation, 2026)

Pollen micromorphology and functional traits as indicators of genetic diversity in Elaeis spp. - M. Neema; S. Suresh; G. Somasundaram; S. G. Silpa; R. P. Premalatha; P. Anitha; G. M. Aswathy (Genetic Resources and Crop Evolution, 2026)

Meta-topolin Stimulates In Vitro Plantlet Generation from Embryonic Shoot Meristem Explants in Coconut (Cocos nucifera) - M. S. Namitha; M. Neema; M. K. Rajesh; M. P. Fathimath Zaeema; Krishna Prakash; K. S. Muralikrishna; Anitha Karun (Agricultural Research, 2026)

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

Toxicity and antiproliferative activity assessment of a novel compound Zr I isolated from Zingiber roseum Rosc - Swarnalatha P.; Deepika Divya K.; Anjali Jha; Anitha M.; S. P. D. Ponamgi; Seema Kumari; Sujatha Peela (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Evaluation of the anti-inflammatory and wound healing potential of Ayapana protein extracted from fresh leaves of Ayapana triplinervis Vahl - In vitro - Anitha P; Balasubramanian Murugesan (Next Research, 2025)

Determining the efficacy of phytoconstituents of Ficus religiosa L. against dermatophytes through invitro and insilico approaches - A. Anitha; P. Ponmurugan; V. Hemamalini; D. Arunkumar (In Silico Pharmacology, 2025)

Transforming waste management: leveraging recycletransformernet for effective recycling strategies - A. Devi; Amirtha Saravanan; R. Reeta; V. P. Anitha (Clean Technologies and Environmental Policy, 2025)

Development of MOF and Cleome Gynandra infused guar gum film: A high- performance antibacterial and antioxidant packaging solution for fruits shelf life extension - P. Ananthi; K. Hemkumar; Anitha Pius (Food Packaging and Shelf Life, 2025)

Short-Term Response of Mandous Severe Cyclone on Coastal Water Quality Along Southwestern Bay of Bengal, India - Subhasis Pradhan; P. Senthilkumar; Umakanta Pradhan; Subrat Naik; Rabindra Kumar Sahoo; Anitha Gera; Uma Sankar Panda; Pravakar Mishra; M. V. Ramana Murthy; P. Vipin Babu (Pure and Applied Geophysics, 2025)

Novel biosynthesized zinc selenite photocatalysts for enhanced degradation of oxytetracycline and Rhodamine B dye with antibacterial activity - A. Anitha; P. Ponmurugan; D. Arunkumar; C. S. Sumathi; M. Sathishkumar; T. Purushothaman (BioMetals, 2025)

Development of reverse transcription recombinase polymerase amplification assay for rapid diagnostics of Peanut mottle virus - B. Parameswari; P. Anbazhagan; A. Rajashree; G. V. Chaitra; Kavi Sidharthan; S. K. Mangrauthia; Faisal Yousuf; K. Anitha; Y. Prasanthi; B. Bhaskar; V. Celia Chalam; G. P. Singh (Physiology and Molecular Biology of Plants, 2025)

Alkaloid-based modulators of the PI3K/Akt/mTOR pathway for cancer therapy: Understandings from pharmacological point of view - Fatima Zohra Mokhfi; Md Al Amin; Mehrukh Zehravi; Sherouk Hussein Sweilam; Uppuluri Varuna Naga Venkata Arjun; Jeetendra Kumar Gupta; Bhaskar Vallamkonda; Anitha Balakrishnan; Manjula Challa; Jyoti Singh; P. Dharani Prasad; Syed Salman Ali; et al. (Chemico-Biological Interactions, 2024)

Correction to: Repurposing of approved antivirals against dengue virus serotypes: an in silico and in vitro mechanistic study - S. H. Rashmi; K. Sai Disha; N. Sudheesh; Kavitha Karunakaran; Alex Joseph; Anitha Jagadesh; P. P. Mudgal (Molecular Diversity, 2024)

Repurposing of approved antivirals against dengue virus serotypes: an in silico and in vitro mechanistic study - S. H. Rashmi; K. Sai Disha; N. Sudheesh; Joseph Karunakaran; Alex Joseph; Anitha Jagadesh; P. P. Mudgal (Molecular Diversity, 2024)
Dengue is an emerging, mosquito-borne viral disease of international public health concern. Dengue is endemic in more than 100 countries across the world. However, there are no clinically approved antivirals for its cure. Drug repurposing proves to be an efficient alternative to conventional drug discovery approaches in this regard, as approved drugs with an established safety profile are tested for new indications, which circumvents several time-consuming experiments. In the present study, eight approved RNA-dependent RNA polymerase inhibitors of Hepatitis C virus were virtually screened against the Dengue virus polymerase protein, and their antiviral activity was assessed in vitro. Schrödinger software was used for in silico screening, where the compounds were passed through several hierarchical filters. Among the eight compounds, dasabuvir was finally selected for in vitro cytotoxicity and antiviral screening. Cytotoxicity profiling of dasabuvir in Vero cells revealed changes in cellular morphology, cell aggregation, and detachment at 50 μM. Based on these results, four noncytotoxic concentrations of dasabuvir (0.1, 0.25, 0.5, and 1 µM) were selected for antiviral screening against DENV-2 under three experimental conditions: pre-infection, co-infection, and post-infection treatment, by plaque reduction assay. Viral plaques were reduced significantly ( p < 0.05) in the co-infection and post-infection treatment regimens; however, no reduction was observed in the pretreatment group. This indicated a possible interference of dasabuvir with NS5 RdRp, as seen from in silico interaction studies, translating into a reduction in virus plaques. Such studies reiterate the usefulness of drug repurposing as a viable strategy in antiviral drug discovery. Graphical Abstract In this drug repurposing study, dasabuvir, a known anti-hepatitis C drug, was selected through virtual screening and assessed for its anti-dengue activity.

Cellulose acetate based-membrane supported by metal-organic frameworks for the removal of diclofenac and ciprofloxacin from polluted water - Ananthi P; Hemkumar K; Manikandan S; Anitha Pius (Groundwater for Sustainable Development, 2024)

Identification of sources of resistance and comparative metabolomic profiling of resistant and susceptible chilli germplasm to Meloidogyne incognita Race 1 - Prasanna Holajjer; T. P. Ahammed Shabeer; M. K. Mahatma; Z. Khan; S. R. Pandravada; N. Sivaraj; Anitha Kodaru; Anita Pardeshi (Australasian Plant Pathology, 2024)

Dual ion specific electrochemical sensor using aminothiazole-engineered carbon quantum dots - P. Keerthana; Ashlay George; M. Bharath; Munmun Ghosh; Anitha Varghese (Chemical Engineering Journal, 2024)

Vegetable grafting: a green technique to combat biotic and abiotic stresses - A. Remzeena; P. Anitha (Vegetos, 2023)

A Simplified Isothermal Recombinase Polymerase Amplification Assay for Detection of Sugarcane bacilliform virus Infection - B. Parameswari; S. K. Sharma; L. Karthikaiselvi; Baby Wangkhem; K. Nithya; R. Viswanathan; G. P. Rao; V. Celia Chalam; K. Anitha (Sugar Tech, 2023)

A novel QTL linked to asparagine synthetase gene for stem height increment in oil palm (E. guineensis Jacq.) identified and validated through integrated genomic approaches - B. Kalyana Babu; R. K. Mathur; G. Ravichandran; P. Anitha; H. P. Bhagya; M. V. B. Venu (Euphytica, 2023)

Targeting Redundant ROBO1 and SDF-1 Pathways Prevents Adult Hemangioblast Derived-EPC and CEC Activity Effectively Blocking Tumor Neovascularization - Anitha K. Shenoy; Liya Pi; Alexander P. Ligocki; Koji Hosaka; Christopher R. Cogle; Edward W. Scott (Stem Cell Reviews and Reports, 2023)

A ratiometric fluorescent sensor based on dual-emissive carbon dot for the selective detection of Cd2+ - P. Keerthana; Avijit Kumar Das; M. Bharath; Munmun Ghosh; Anitha Varghese (Journal of Environmental Chemical Engineering, 2023)

Coupled physical-biogeochemical simulations of upwelling, ecological response to fresh water - Anitha Gera; R Gayathri; P Ezhilarasan; V Ranga Rao; M V Ramana Murthy (Ecological Modelling, 2023)

Genetic mapping of drought tolerance traits phenotyped under varying drought stress environments in peanut (Arachis hypogaea L.) - Subhasini Ghosh; Supriya S. Mahadevaiah; S. Anjan Gowda; Sunil S. Gangurde; Mangesh P. Jadhav; Anil A. Hake; P. Latha; T. Anitha; V. P. Chimmad; Kiran K. Mirajkar; Vinay Sharma; Manish K. Pandey; et al. (Euphytica, 2022)

An Efficient Inclusion Complex Based Fluorescent Sensor for Mercury (II) and its Application in Live-Cell Imaging - Keerthana P; Hanna Abbo; Anila Rose Cherian; Salam Titinchi; Anitha Varghese (Journal of Fluorescence, 2022)

Phenomics, genomics of oil palm (Elaeis guineensis Jacq.): way forward for making sustainable and high yielding quality oil palm - B. Kalyana Babu; R. K. Mathur; P. Anitha; G. Ravichandran; H. P. Bhagya (Physiology and Molecular Biology of Plants, 2021)

First report on the association of ‘Candidatus Phytoplasma asteris’ with lethal wilt disease of coconut (Cocos nucifera L.) in India - Merin Babu; S. Thangeswari; A. Josephrajkumar; V. Krishnakumar; A. Karthikeyan; V. Selvamani; Mol Daliya; Vinayaka Hegde; H. P. Maheswarappa; Anitha Karun (Journal of General Plant Pathology, 2021)

Multi-class diagnosis of Alzheimer’s disease using cascaded three dimensional-convolutional neural network - Manu Raju; Varun P. Gopi; V. S. Anitha; Khan A. Wahid (Physical and Engineering Sciences in Medicine, 2020)

Automated segmentation of optic disc using statistical region merging and morphological operations - K. S. Nija; C. P. Anupama; Varun P. Gopi; V. S. Anitha (Physical and Engineering Sciences in Medicine, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Increasing incidence of tomato big bud phytoplasma in Ranga Reddy District of Telangana State, India - Madhupriya; D. Anitha Kumari; D. S. Vennila; M. Narayana Bhat; G. P. Rao (Indian Phytopathology, 2018)

Depth of soil compaction predominantly affects rice yield reduction by reproductive-stage drought at varietal screening sites in Bangladesh, India, and Nepal - Suresh Prasad Singh; Abhinav Jain; M. S. Anantha; Santosh Tripathi; Subarna Sharma; Santosh Kumar; Archana Prasad; Bhawana Sharma; Biswajit Karmakar; Rudra Bhattarai; Sankar Prasad Das; Shravan K. Singh; et al. (Plant and Soil, 2017)

The Neuropeptide Orexin-A Inhibits the GABAA Receptor by PKC and Ca2+/CaMKII-Dependent Phosphorylation of Its β1 Subunit - Divya Sachidanandan; Haritha P. Reddy; Anitha Mani; Geoffrey J. Hyde; Amal Kanti Bera (Journal of Molecular Neuroscience, 2017)

A Preliminary Report on the Butterfly Diversity of Kurumpuram Reserve Forest, Marakkanam, Tamil Nadu - K. Silambarasan; K. Sujatha; A. Anitha Joice; P. Senthilkumaar; E. Rajalakshmi (Proceedings of the Zoological Society, 2016)

De novo assembly and characterization of global transcriptome of coconut palm (Cocos nucifera L.) embryogenic calli using Illumina paired-end sequencing - M. K. Rajesh; T. P. Fayas; S. Naganeeswaran; K. E. Rachana; U. Bhavyashree; K. K. Sajini; Anitha Karun (Protoplasma, 2016)

Gene and Protein Network Analysis of AmpC β Lactamase - P. Anitha; Susmita Bag; Anand Anbarasu; Sudha Ramaiah (Cell Biochemistry and Biophysics, 2015)

Simultaneous detection of groundnut rosette assistor virus (GRAV), groundnut rosette virus (GRV) and satellite RNA (satRNA) in groundnuts using multiplex RT-PCR - S. Anitha; E. S. Monyo; P. Okori (Archives of Virology, 2014)

Molecular characterization of Indian isolate of peanut mottle virus and immunodiagnosis using bacterial expressed core capsid protein - K. Soumya; M. Yogita; Y. Prasanthi; K. Anitha; P. B. Kavi Kishor; R. K. Jain; Bikash Mandal (VirusDisease, 2014)

Shallow geological environment of Krishna–Godavari offshore, eastern continental margin of India as inferred from the interpretation of high resolution sparker data - G ANITHA; M V RAMANA; T RAMPRASAD; P DEWANGAN; M ANURADHA (Journal of Earth System Science, 2014)

Scope of novel and rare bulbiferous coconut palms (Cocos nucifera L.) - B. A. Jerard; M. K. Rajesh; S. A. Elain; K. K. Sajini; Shafeeq Rahman; T. P. Fayas; Anitha Karun (Genetic Resources and Crop Evolution, 2014)

Pollen morphology of the three subgenera of Alnus - Estella B. Leopold; Joshua Birkebak; Linda Reinink-Smith; Anitha P. Jayachandar; Paula Narváez; Stephanie Zaborac-Reed (Palynology, 2012)

Application of Isozyme Data in Fingerprinting Napier Grass (Pennisetum purpureum Schum.) for Germplasm Management - Anitha P. Bhandari; D. H. Sukanya; C. R. Ramesh (Genetic Resources and Crop Evolution, 2006)

Arterial blood gas management during cardiopulmonary bypass - O. P. Sanjay; Anitha Devnath; B. C. Thejas (Indian Journal of Clinical Biochemistry, 2005)

Glutathione S-transferase M1 and T1 null genotype distribution in South Indians - A.T. Naveen; C. Adithan; N. Padmaja; C.H. Shashindran; B.K. Abraham; K. Satyanarayanamoorthy; P. Anitha; N. Gerard; R. Krishnamoorthy (European Journal of Clinical Pharmacology, 2004)

Membrane associated estrogen receptors and related proteins: Localization at the plasma membrane and the endoplasmic reticulum - Anitha P. Govind; Raghava Varman Thampan (Molecular and Cellular Biochemistry, 2003)